How the Science of Reading Informs 21st‐Century Education. (6th September 2020) - Petscher, Yaacov; Cabell, Sonia Q.; Catts, Hugh W.; Compton, Donald L.; Foorman, Barbara R.; Hart, Sara A.; Lonigan, Christopher J.; Phillips, Beth M.; Schatschneider, Christopher; Steacy, Laura M.; Terry, Nicole Patton; Wagner, Richard K.
ABSTRACT: The science of reading should be informed by an evolving evidence base built on the scientific method. Decades of basic research and randomized controlled trials of interventions and instructional routines have formed a substantial evidence base to guide best practices in reading instruction, reading intervention, and the early identification of at‐risk readers. The recent resurfacing of questions about what constitutes the science of reading is leading to misinformation in the public space that may be viewed by educational stakeholders as merely differences of opinion among scientists. The authors' goals in this article were to revisit the science of reading through an epistemological lens to clarify what constitutes evidence in the science of reading, and to offer a critical evaluation of the evidence provided by the science of reading. To this end, the authors summarize those things that they believe have compelling evidence, promising evidence, or a lack of compelling evidence. The authors conclude with a discussion of areas of focus that they believe will advance the science of reading to meet the needs of all students in the 21st century.